Roberta Vilka fotogrāfija - Beveronija (Beveronija, 1930)
Latvijas Universitātes Studentu padomes priekšsēdētāja (1934-1936), LU Tautsaimniecības un tiesību zinātņu fakultātes Tautsaimniecības nodaļas studenta (1924-1940) un latviešu studentu korporācijas Beveronija seniora (1932) Roberta Vilka fotogrāfija.

Photograph by Robert Vilks, Chairman of the Student Council of the University of Latvia (1934-1936), student of the Department of Economics of the Faculty of Economics and Law (1924-1940), and senior of the Latvian Student fraternity Beveronija (1932).
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Latviešu studentu korporācija "Beveronija"; Studentu akadēmiskās mūža organizācijas; Studentu korporācijas -- Latvijas Universitāte; Latvijas Universitātes Studentu padome; Studentu akadēmiskā dzīve; The University of Latvia; Student academical lifetime organisations; Student fraternities; Student Council of the University of Latvia